Design of Enzymatically Cleavable Prodrugs of a Potent Platinum‐Containing Anticancer Agent. Issue 49 (10th October 2014) - Ding, Song; Pickard, Amanda J.; Kucera, Gregory L.; Bierbach, Ulrich
Abstract Using a versatile synthetic approach, a new class of potential ester prodrugs of highly potent, but systemically too toxic, platinum–acridine anticancer agents was generated. The new hybrids contain a hydroxyl group, which has been masked with a cleavable lipophilic acyl moiety. Both butanoic (butyric) and bulkier 2‐propanepentanoic (valproic) esters were introduced. The goals of this design were to improve the drug‐like properties (e.g., logD) and to reduce the systemic toxicity of the pharmacophore. Two distinct pathways by which the target compounds undergo effective ester hydrolysis, the proposed activating step, have been confirmed: platinum‐assisted, self‐immolative ester cleavage in a low‐chloride environment (LC‐ESMS, NMR spectroscopy) and enzymatic cleavage by human carboxylesterase‐2 (hCES‐2) (LC‐ESMS). The valproic acid ester derivatives are the first example of a metal‐containing agent cleavable by the prodrug‐converting enzyme. They show excellent chemical stability and reduced systemic toxicity. Preliminary results from screening in lung adenocarcinoma cell lines (A549, NCI‐H1435) suggest that the mechanism of the valproic esters may involve intracellular deesterification.